To What Extent Do Teachers of Gifted Students Identify Inner and Intermodal Relations in Knowledge Representation? - Costu, Bayram; Gül, Davut (Universitas Pendidikan Indonesia, 2021)
Gifted students get bored of reading authoritative and descriptive multimodal texts. They need coherent, explanatory, and interactive texts. Moreover, because of the pandemic, gifted students took courses online, and teachers had to conduct their lessons on digital online tools with multimodal representations. They posted supplementary teaching materials as multimodal texts to the students. Hence, teachers of gifted students should pay attention to inner and intermodal relations to meet the needs of gifted students and support their learning experience. The research aims at examining to what extent teachers of gifted students identify inner and intermodal relations because before designing these relations, the teacher should recognize these types of relations. The educational descriptive case study was applied. Six experienced primary school teachers were involved. The data were analyzed via content analysis. The results showed that teachers just identified the primitive level of inner and intermodal relations. The conclusion can be drawn that several educational design research should be increased to construct professional development courses for teachers about this issue. Learning and applying inner and intermodal relations are crucial for teachers of gifted students, in addition to having curiosity, they have a high cognitive level in different areas, thus they demand advanced forms of multimodal texts.